LEGAL ANALYSIS OF DETERMINATION OF ULAYAT LAND IN KAMPUNG NEGARA BATIN SUB-DISTRICT OF NEGARA BATIN, WAY KANAN REGENCY BASED ON ARTICLE 5 OF THE PRINCIPAL AGRARIAN LAW OF 1960 - Nopan Wijaya (Indonesian Journal of Law and Policy Studies, 2021)
Land is a very basic human need. Humans live in carrying out activities on the ground so that every time humans are always in contact with the ground, it can be said that almost all activities of human life, either directly or indirectly, always require land. Land has a very important role in the life of the Indonesian nation or in the implementation of national development which is held as a sustainable effort to create a just and prosperous society based on Pancasila and the 1945 Constitution of the Republic of Indonesia. legal recognition and the supporting and inhibiting factors for the determination of ulayat land in the Negara Batin Village, Negara Batin District, Way Kanan Regency, Lampung Province. The research method used in this study is a normative juridical approach and an empirical approach. The normative juridical approach is defined as an approach to the legal rules related to the determination of customary land based on Article 5 of the Basic Agrarian Law of 1960. While the empirical approach is intended as an attempt to approach the problem under study with a real legal nature or in accordance with the reality in society.